Analisis Pengaruh Perceived Usefulness terhadap Continuance Intention pada Siswa SMA - Kurnia Adityarini Putri Handayani; Silsyano Modiwirijo (International Journal of Learning and Education, 2026)
This research evaluates the determinants of Learning Management System (LMS) continuance intention among high school students. Grounded in the Stimulus-Organism-Response (S-O-R) framework, the study investigates the specific impact of Perceived Usefulness (PU) on Continuance Intention (CIT). Data from 403 students in Semarang, Indonesia, were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The statistical results confirm that Perceived Usefulness significantly predicts Continuance Intention (beta = 0.530, p < 0.001). The structural model exhibits substantial predictive power, explaining 77.2% of the variance (R2 = 0.772). These findings suggest that to ensure digital sustainability, educational platforms must prioritize delivering tangible functional benefits to students.